2000
DOI: 10.1007/s100670070040
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Fibromyalgia Benefit from Aerobic Endurance Exercise

Abstract: Fibromyalgia (FM) is a disorder characterised by diffuse widespread musculoskeletal aching and stiffness and multiple tender points [1]. Its pathophysiology is poorly understood. The influence of aerobic endurance exercise on pain in patients with FM was investigated. Twenty-seven patients (25 female, 2 male) participated in a controlled clinical study and performed 12 weeks of jogging, walking, cycling or swimming following a given schedule. Twelve sedentary FM patients (11 female, 1 male) served as controls.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(34 citation statements)
references
References 26 publications
4
25
0
5
Order By: Relevance
“…Firstly, it should be taken into account that FMS patients apparently perceive pain to be caused by strain, which leads them to avoid any exercise, thus causing more pain. 35 The flexibility training proposed may have minimized muscular pain, breaking the relationship proposed in musculoskeletal conditions such as FMS, where depression, pain, and disability lead to a cycle of poor mental and physical health. 36 Therefore, our patients may have lost their fear of exercise and led a more active life, thereby to some extent reducing their fatigue levels.…”
Section: Impact Of the Illnessmentioning
confidence: 99%
“…Firstly, it should be taken into account that FMS patients apparently perceive pain to be caused by strain, which leads them to avoid any exercise, thus causing more pain. 35 The flexibility training proposed may have minimized muscular pain, breaking the relationship proposed in musculoskeletal conditions such as FMS, where depression, pain, and disability lead to a cycle of poor mental and physical health. 36 Therefore, our patients may have lost their fear of exercise and led a more active life, thereby to some extent reducing their fatigue levels.…”
Section: Impact Of the Illnessmentioning
confidence: 99%
“…Meiworm et al compared 27 patients undergoing aerobic exercise training with 12 sedentary controls [29]. The exercise group undertook a self-managed programme of walking, jogging, cycling and swimming, for an average of 25 minutes, two to three times a week.…”
Section: Exercisementioning
confidence: 99%
“…Although there were significant gains in psychologic well-being, the authors reported that they were "modest and ill-sustained" and neither group improved their pain report over baseline. Meiworm et al [29] and Busch et al [30] showed favorable results with their homebased programs, improving performance and pain and function and illness severity, respectively.…”
Section: Variations In Exercise Intensity and Program Designmentioning
confidence: 96%